2006
DOI: 10.1182/blood-2005-11-056689
|View full text |Cite
|
Sign up to set email alerts
|

The β-tail domain (βTD) regulates physiologic ligand binding to integrin CD11b/CD18

Abstract: Crystallographic and electron microscopy studies revealed genuflexed (bent) integrins in both unliganded (inactive) and physiologic ligandbound (active) states, suggesting that local conformational changes are sufficient for activation. Herein we have explored the role of local changes in the contact region between the membrane-proximal ␤-tail domain (␤TD) and the ligand-binding ␤A domain of the bent conformation in regulating interaction of integrin CD11b/CD18 (␣M␤2) with its physiologic ligand iC3b.We replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 50 publications
3
53
1
Order By: Relevance
“…It has been reported that replacing the ␤2 CD loop sequence with the homologous ␤3 sequence or inserting a N-glycan-binding site in the CD loop in ␣M␤2 integrin induced robust ligand binding (27). However, the fact that the deletion of the CD loop of the ␤T domain failed to activate ␣IIb␤3 in our experiment strongly argues against the deadbolt theory, in which an endogenous ␤A/␤T interface interaction plays a critical role in maintaining integrin in its low affinity state.…”
Section: Discussioncontrasting
confidence: 55%
“…It has been reported that replacing the ␤2 CD loop sequence with the homologous ␤3 sequence or inserting a N-glycan-binding site in the CD loop in ␣M␤2 integrin induced robust ligand binding (27). However, the fact that the deletion of the CD loop of the ␤T domain failed to activate ␣IIb␤3 in our experiment strongly argues against the deadbolt theory, in which an endogenous ␤A/␤T interface interaction plays a critical role in maintaining integrin in its low affinity state.…”
Section: Discussioncontrasting
confidence: 55%
“…Therefore, we conclude that the ␤-tail domain CD loop does not regulate ligand binding and does not act as a deadbolt. Recently, it was reported that exchanging D658GMD in the ␤-tail domain CD loop of the ␤2 subunit with D672SSG of the ␤3 subunit or with N658GTD, which introduces a glycan wedge sequence, activated the ␣M␤2 integrin (43). A crystal structure of ␣M␤2 is not available.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that the CDloop acts as a deadbolt, preventing integrin activation by locking βA in an inactive state. Indeed, a number of antibodies that activate β1 integrins bind to the βTD or the βA interface, and the βTD has been shown to regulate ligand binding (27,29). We propose that asTF induces the removal of the CD-loop deadbolt.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that asTF induces a conformational change in β1 integrins that render them prone to activation, as we used a β1 integrin-blocking antibody that is reactive with the membrane-proximal β-tail domain (βTD) of the β1 integrin subunit, and the 579-799 integrin peptide features this domain. The βTD contains a CD-loop that contacts the ligand-binding integrin βA domain and the hybrid domain, and this contact is lost upon integrin activation (27,28). It has been postulated that the CDloop acts as a deadbolt, preventing integrin activation by locking βA in an inactive state.…”
Section: Discussionmentioning
confidence: 99%